Managing diabetes in the psychiatric in-patient setting: knowledge, attitudes and skills of healthcare professionals - Zoe Goff; Vishal Sharma; Ioana Varvari (BJPsych Bulletin)
Aims and method There is currently a lack of monitoring and standardisation of diabetes care in the National Health Service (NHS) psychiatric in-patient setting. We surveyed healthcare professionals in psychiatric in-patient units across England to understand current diabetes care. A 13-item questionnaire was piloted via think-aloud interviews. The survey was completed by healthcare professionals across 19 wards in 11 NHS mental health trusts. Results were analysed via descriptive statistics and thematic analysis.